Effects of endovenous laser ablation on vascular tissue: molecular genetics approach - Alur, İhsan (Int J Clin Exp Med, 2015)
Background: Endovenous laser ablation (EVLA) is a treatment option for lower extremity varicose veins. In the present study, we investigate to the genetic changes and possibility of living tissue in the saphenous vein wall after the EVLA procedure. Methods: Eleven saphenous vein grafts were randomized in two groups: (1) 4 cm SVG segments of performed EVLA procedure in study group, (2) 4 cm segments of SVG none performed EVLA procedure in control group. SVG were taken from the remnants of distal saphenous vein grafts prepared for the bypass procedure but not used. SVG was approximately 8 cm in length and was divided into two parts 4 cm in length. One half was exposed to laser energy, while the other half of the same vein graft was untreated as a control. EVLA was performed on complete saphenous veins in the study group. Abnormal genetic changes of the SVG were observed with a Tri-Reagent method and quantified with a Nanodrop™ spectrophotometer. Results: Histopathological changes indicated that the intima including the endothelium was completely necrotized in the study group. It was observed that intimal thermal-energy-induced injury did not reach the media. Histopathological examination showed that homogenous eosinophilic discoloration and coagulation necrosis characterized the laser related thermal damage as well. Conclusions: In this preliminary study, we found that living tissue remained in the SVG wall after application of laser ablation, and we also detected abnormal genetic changes in the study group compared with the control group.